2015
DOI: 10.1017/s1368980015001019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heterogeneity in types of vegetables served by main household food preparers and food decision influencers

Abstract: Objective: While vegetables are often studied as one food group, global measures may mask variation in the types and forms of vegetables preferred by different individuals. To explore preferences for and perceptions of vegetables, we assessed main food preparers based on their preparation of eight specific vegetables and mushrooms. Design: An online self-report survey. Setting: Ontario, Canada. Measures included perceived benefits and obstacles of vegetables, convenience orientation and variety seeking in meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Yi et al . ( 40 ) , however, show that the perception of specific vegetables on taste, healthiness, ease of preparation and cost varies significantly across different consumer segments. This has implications for the development of new approaches to promoting different vegetables.…”
Section: Strategies To Increase Fruit and Vegetable Intake: What Work?mentioning
confidence: 99%
See 1 more Smart Citation
“…Yi et al . ( 40 ) , however, show that the perception of specific vegetables on taste, healthiness, ease of preparation and cost varies significantly across different consumer segments. This has implications for the development of new approaches to promoting different vegetables.…”
Section: Strategies To Increase Fruit and Vegetable Intake: What Work?mentioning
confidence: 99%
“…In addition, a study from Peru (39) found that promoting fruit consumption by product placement close to the point of purchase, adding health information and price reduction had a positive effect on fruit purchasing in a university cafeteria, especially in males and non-student adults. Yi et al (40) , however, show that the perception of specific vegetables on taste, healthiness, ease of preparation and cost varies significantly across different consumer segments. This has implications for the development of new approaches to promoting different vegetables.…”
mentioning
confidence: 99%